A novel approach to spinal anaesthesia to avoid aerosol‐generating procedures in a patient with COVID‐19 presenting for laser prostate surgery. Issue 2 (16th October 2020) - Oon, Z.; Ha, C.
Summary: General anaesthesia involves aerosol‐generating procedures which, in the context of the coronavirus 2019 (COVID‐19) pandemic, increases the risk of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) transmission from patients to staff. This risk can be minimised by performing spinal or regional anaesthesia instead of general anaesthesia where possible. We report the successful management of a patient utilising spinal anaesthesia in a patient with COVID‐19 undergoing urgent holmium laser enucleation of prostate for symptomatic benign prostatic hyperplasia. A combination of bupivacaine, diamorphine and midazolam was administered intrathecally which provided adequate anaesthesia despite the prolonged surgical duration. Nebulised lidocaine was also given to prevent coughing during the procedure. This report demonstrates that it is possible and safe to use spinal anaesthesia to perform prolonged surgical procedures that are normally conducted under general anaesthesia using a combination of intrathecal adjuncts to facilitate effective block duration. In addition, the novel use of nebulised lidocaine for its antitussive effects in a patient with COVID‐19 is highlighted.